Irreversibility analysis of Magnetohydrodynamic (MHD) mixed convection flow of viscoelastic hybrid nanofluid flow in a channel - Padma Ummeda; Surender Ontela (Chemical Engineering Journal Advances, 2023)
This manuscript delves into the analysis of irreversibility in Magnetohydrodynamic (MHD) mixed convection flow of a viscoelastic hybrid nanofluid within a vertical channel. The study adopts a parallel plate configuration and employs Aluminum oxide (Al2O3) and Titanium oxide (TiO2) nanoparticles dispersed in a Carboxymethyl cellulose (CMC)-water base fluid. Utilizing similarity transformations, the governing partial differential equations (PDEs) are converted into a set of ordinary differential equations (ODEs), streamlining the mathematical model. These ODEs are then solved using the homotopy analysis method via Mathematica software for various governing parameter values. Key parameters including the Brinkman number, volume fractions of nanoparticles, magnetic effects, and wall temperature parameter are systematically investigated. Noteworthy insights include that volume fraction and magnetic parameter augments velocity at the left wall and slows down it toward the right wall; Brinkman number and wall temperature parameters significant in elevating temperature; Entropy and Bejan number respond differently to variations in the Brinkman number. Entropy escalates with increasing magnetic parameter, while the Bejan number declines. Illustrated through graphs, these findings enrich the comprehension of MHD mixed convection flow and heat transfer in viscoelastic hybrid nanofluids, elucidating irreversibility aspects tied to such systems.